Derivation of dopaminergic neurons from embryonic and induced pluripotent stem cells - Williams, Emma (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2011)
Dopamine (DA) neurons have several fundamental functions in the brain, dysfunction of which has been implicated in neurological and psychiatric disorders, including Parkinson’s disease (PD) and schizophrenia. Embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) may provide an unlimited source of DA neurons for in vitro studies as they can be propagated indefinitely in culture in an undifferentiated state while retaining pluripotency. Interest has also focused on the use of DA neurons derived from these cells for regenerative medicine in PD. However, the potential of ESCs and iPSCs is greatly hindered by the heterogonous nature of cultures even after directed differentiation, with multiple cell types often of more than one germ layer being present. This may be partly or wholly overcome by expression of a marker, such as enhanced green fluorescent protein (EGEP), from a cell specific promoter, thus allowing both the selection of a particular cell type from a mixed cell population by fluorescent activated cell sorting (FACS) and differentiation to be followed in real time in live cells.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin